Diagnostic imaging of benign and malignant osseous tumors of the fingers - Melamud, Kira; Drape, Jean-Luc; Hayashi, Daichi; Roemer, Frank; Zentner, Joachim; Guermazi, Ali (Radiographics, 2014)
Primary lesions of the tubular bones of the digits are not uncommon, and the vast majority of these lesions are benign. Benign intramedullary lesions such as enchondromas are frequently discovered incidentally, unless they are associated with a pathologic fracture. Expansile lesions or lesions that are pedunculated and protrude from the cortex may manifest with pain and functional deficits from local inflammatory reactions. Systemic disorders such as sarcoidosis and local soft-tissue lesions with involvement of adjacent bone may mimic primary phalangeal bone tumors. Primary or secondary malignant lesions of the phalanges, most commonly chondrosarcomas, are extremely rare, and their characterization may require the use of multiple modalities, including radiography, computed tomography, and magnetic resonance imaging. Although ultrasonography is extremely useful in the evaluation of soft-tissue lesions of the hand, its role in the evaluation of osseous lesions is limited. The authors describe the imaging features of the most common benign osseous and chondral lesions of the fingers, including enchondromas, cystic lesions, and osteochondromas. In addition, they discuss malignant entities that may occur in the fingers (eg, chondrosarcomas and metastatic lesions) and commonly encountered mimics of primary osseous lesions (eg, glomus tumors, intraosseous epidermal inclusion cysts, infectious entities, and manifestations of systemic diseases). They also discuss the advantages and disadvantages of the most commonly used imaging modalities in differentiating benign from malignant lesions.
EVALuna2:14444